Adopsi E-Katalog Pengadaan Barang Dan Jasa Pada Umkm Kabupaten Banjar Menggunakan Technology Accaptence Model (TAM) - Rahmatullah, Ahyar; Budiman, Arief (JWM (JURNAL WAWASAN MANAJEMEN), 2024)
The purpose of this research is to explain and analyze E-Catalog Adoption in Banjar Regency UMKM using the Technology Acceptance Model (TAM) which consists of exogenous variables namely Perceived Usefulness, Perceived Ease of Use and endogenous variables namely Attitude Toward Using, Behavioral Intention and Actual Use. The respondents in this study were 341 UMKM registered in the Banjar Regency E- Catalog This research uses the SEM (Structural Equation Model) analysis method using Partial Least Square (PLS). The results of this research show that 4 hypotheses are accepted, namely the Perceived usefulness variable has a significant effect on Attitude Toward Using, Perceived Ease of Use has a positive and significant effect on Attitude Toward Using, Perceived Ease of Use has a positive and significant effect on Behavioral Intention, and Behavioral Intention has a positive and significant effect. significant to Actual Usage. Meanwhile, there were 2 hypotheses that were rejected, namely Perceived Usefulness had no significant effect on Behavioral Intention and Attitude Toward Using had no significant effect on Behavioral Intention of the Banjar Regency UMKM E-Catalog.